Profile and origins of consumers in street commerce and services in Salvador-Bahia (Brazil): a geographical approach - Angelo Serpa; Leite, Wellington; Machado, Juliana (Geografares, 2023)
This article introduces a geographical approach to analyze the profile of consumers of commerce and street services in the city of Salvador, the capital of the state of Bahia. Building upon previous research and field surveys conducted in specific spatial sections of this city (SERPA; LEITE; MACHADO, 2019, 2021), this study delves deeper into understanding these dynamics. Moreover, this paper outlines the research methodology and strategies employed in conducting surveys during the period of social distancing caused by the COVID-19 pandemic. The findings regarding the profile of consumers reveal important aspects of the interplay between the upper and lower circuits of the economy (SANTOS, 2004). Furthermore, these activities not only foster social interaction but also underscore the street’s significance as a communal space, essential for public sociability, even in times of social isolation.